17‐allylamino‐17‐demethoxygeldanamycin impeded chemotherapy through antioxidant activation via reducing reactive oxygen species‐induced cell death. Issue 2 (30th October 2018) - Li, Yueqi; Chen, Yiyang; Qiu, Cen; Ma, Xiaoying; Lei, Kecheng; Cai, Guoxiang; Liang, Xin; Liu, Jianwen
Abstract: Hyperthermia enhances the anticancer effects of thymidylate synthase (TYMS) inhibitors (raltitrexed, RTX) and improves the precise biochemical mechanisms partially through enhancement of intracellular drug absorption. Recent research focuses on the potential anticancer drug target Heat Shock Protein 90 (HSP90), which could increase the sensitivity of cancer cells to TYMS inhibitors; however, with different HSP90 inhibitors, several research studies finally showed a poor efficacy in preclinical or clinical research. Here, we showed that 17‐allylamino‐17‐demethoxygeldanamycin (17‐AAG, HSP90 inhibitor) affects the efficacy of chemotherapy through antioxidant activation–induced resistance. In this study, we found that RTX, alone or in combination with hyperthermia, triggers reactive oxygen species (ROS) exposure and thus induces cell death. Also, the addition of hyperthermia showed more ROS exposure and function. The pharmacologic inhibition of HSP90 reversed the effects of chemotherapeutical treatments, while the overexpression of HSP90 showed no relation with these effects, which demonstrated that dysregulation of HSP90 might have a significant impact on chemotherapeutic treatments. The addition of 17‐AAG increased the activation of antioxidant with increased antioxidant enzymes, thus affecting the RTX efficacy. Abstract : The addition of hyperthermia further induces raltitrexed (RTX) efficacy by reactive oxygen species (ROS)‐induced cell death in human colorectal cancer. In addition, the Heat shock proteins 9 (HSP90) inhibitor impeded chemotherapy through antioxidant activation via reducing ROS‐induced cell death.